Progress and stagnation: A comparative study of gender representation in Chinese language textbooks for junior high school between 2001 edition and 2023 edition - Xia Yang; Yu Sun; Hu He (PLoS ONE, 2025)
Gender bias in textbooks is a global problem. Gender development stands as a pivotal concern among junior high school students, underscoring the paramount importance of scrutinizing gender portrayals within textbooks. Chinese language textbooks, utilized by around 200 million students, have garnered scant attention in English literature concerning its embedded gender ideology. This essay delves into a comparative analysis of gender representations in Chinese Language textbooks published by the People’s Education Press in 2001 and 2023, revealing little advancements. The evolution of these textbooks has witnessed a surge in the number of female authors and an expansion of gender-centric themes, fostering a more diverse array of female roles. However, a discernible disparity persists in the frequency of male and female portrayals, with males continuing to dominate the narrative, even amidst a slight decline in the female proportion. Furthermore, the spectrum of gender roles and professions remains limited, perpetuating the age-old gender binary of “men as providers, women as homemakers.” Notably, societal stereotypes of both genders linger, impeding the depiction of nuanced and multifaceted identities. In summary, this study found that both sets of Chinese language textbooks implicitly contain gender bias, with little progress made towards gender equality, and even has stagnated or declined.